2006
DOI: 10.1103/physrevd.73.094015
|View full text |Cite
|
Sign up to set email alerts
|

Kramers-Moyall cumulant expansion for the probability distribution of parallel transporters in quantum gauge fields

Abstract: A general equation for the probability distribution of parallel transporters on the gauge group manifold is derived using the cumulant expansion theorem. This equation is shown to have a general form known as the Kramers-Moyall cumulant expansion in the theory of random walks, the coefficients of the expansion being directly related to nonperturbative cumulants of the shifted curvature tensor. In the limit of a gaussian-dominated QCD vacuum the obtained equation reduces to the well-known heat kernel equation o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In [11] it was shown that the most general form of the diffusion equation for the probability distribution of the holonomies g [C] on the gauge group manifold is:…”
Section: Free Random Walks On the Group Manifoldmentioning
confidence: 99%
See 4 more Smart Citations
“…In [11] it was shown that the most general form of the diffusion equation for the probability distribution of the holonomies g [C] on the gauge group manifold is:…”
Section: Free Random Walks On the Group Manifoldmentioning
confidence: 99%
“…The term with first-order derivative is prohibited in ( 5) by gauge invariance. It was shown in [11] that the coefficients η a1...a k [C] are directly related to the cumulants of the shifted curvature tensor F a µν , which are the basic objects in the method of field correlators [4]. This relation can be formally written as [11]:…”
Section: Free Random Walks On the Group Manifoldmentioning
confidence: 99%
See 3 more Smart Citations